ENHANCING COMMUNITY EMERGENCY AWARENESS THROUGH BARANGAY COMMONWEALTH FREE BASIC LIFE SUPPORT TRAINING PROGRAM (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Basic Life Support (BLS) is an essential primary healthcare response to medical emergencies and natural disasters, requiring proper knowledge and execution, especially in public settings. The Emergency Response Team (ERT) plays a crucial role in emergency preparedness and response. According to the Red Cross, BLS refers to the immediate care provided by first responders or healthcare professionals in cases of cardiac arrest, respiratory distress, or airway obstruction. Natural disasters, such as fires, floods, and accidents, necessitate a well-prepared community. This study aims to assess the effectiveness of Barangay Commonwealth’s free BLS training program in enhancing emergency preparedness and response among its residents. This study was conducted in Barangay Commonwealth, Quezon City, to evaluate the effectiveness of the BLS training course. The study involved 50 respondents: 15 Barangay personnel, 20 community residents, and 15 members of the Emergency Response Team. A quantitative descriptive research design was utilized to describe and interpret data on the community’s emergency preparedness and response capabilities. Respondents strongly support various strategies to enhance emergency response, including reducing traffic congestion, improving preparedness, promoting inter-agency collaboration, supporting responder mental health, and engaging the community in disaster preparedness. Findings emphasize the necessity of a well-coordinated and efficient emergency response approach. Regular training and drills are recommended to assess the effectiveness of implemented strategies. Barangay Commonwealth has an established Emergency Response Team with adequate BLS training to respond effectively in emergencies. The barangay’s health system actively engages in policies and plans to minimize the adverse effects of disasters. Additionally, the ERT plays a crucial role in educating the public on emergency preparedness, ensuring that the community can respond efficiently to emergencies. Strengthening public awareness and continuous skill development are essential for building a resilient community.
Keywords: basic life support; emergency response; disaster preparedness; community awareness; training program